Hydrodynamic performance of a novel suturelessprosthetic aortic valve - K. Yu. Klyshnikov; E. A. Ovcharenko; Yu. A. Kudryavtseva; L. S. Barbarash (Вестник трансплантологии и искусственных органов, 2020)
The aim of the study was an in vitro hydrodynamic study of the developed prosthetic heart valve of the second generation, designed to carry out an implantation using «valve-in-valve» method. Material and methods. Prototypes of the developed prosthesis were studied under simulated physiological conditions of the heart using a Vivitro Labs pulse duplicator (Canada) in a comparative aspect with «UniLine» clinical commercial aortic valve bioprosthesis (Russia). Samples were tested by simulating sutureless implantation procedure. Results. The developed valves showed satisfactory hydrodynamic characteristics – for all cases of «implantation» from the position of the average trans-prosthetic gradient (6.1–11.1 mm Hg) and the effective orifice area (1.60–1.81 cm2 ). The analysis of the regurgitation fraction allowed us to determine the optimal sizes for implantation using «valvein-valve» method, which subsequently will form the basis of sizing guidelines for size selection. A qualitative analysis of the leaflet’s work demonstrated the presence of slight asymmetry for a number of prostheses – in case of mismatch of sizes when simulating «valve-in-valve» procedure. Conclusion. The tests demonstrate the viability of the developed design from the standpoint of hydrodynamic efficiency and determines the basic rules of selecting a prosthesis for reimplantation relative to the primary valve.